Governmental budgetary reporting systems in the European Union: is the accounting basis relevant for the deficit reliability? - Jesus, M. A. (2015)
When reporting to EUROSTAT for the purpose of deficit assessment, EU member-States follow National Accounts (NA) rules, specifically the European System of National and Regional Accounts. However, the information reported is gathered from Governmental Accounting (GA), namely budgetary reporting. Consequently, several adjustments are needed when translating data from GA into NA, including those concerning the accounting basis – in some countries GA budgetary balance is already accrual-based while in others it is still cash-based. This research aims to analyse adjustments derived from different accounting bases adopted in GA and NA, demonstrating their diversity and materiality and the consequences for EU member-States’ deficit/surplus reliability. It analyses cash-accrual adjustments to be made in Central Government data, using a few EU countries and data from the respective Excessive Deficit Procedure notifications covering the years 2005 to 2010. The main findings show that cash-accrual adjustments are more diverse and tend to be material in relation to the final deficit/surplus, in countries still adopting cash-based budgetary reporting in GA, raising questions concerning the reliability of the deficit/surplus they report.